PENERAPAN MEDIA ALAT PERAGA KONKRET ULAR TANGGA JARIMATIKA UNTUK MENINGKATKAN PEMAHAMAN HITUNG DASAR MATEMATIKA SISWA KELAS IV SDN BHAKTIKARYA - Bayu Putra Winata; Bahtiyar Heru Susanto (STKIP Subang, 2026)
This study aims to improve students’ understanding of basic arithmetic operations in mathematics through the application of concrete teaching aids in the form of the Jarimatika Snake and Ladder game for fourth-grade students at SDN Bhaktikarya. The research method used was Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 21 fourth-grade students of SDN Bhaktikarya. Data were collected through observations of students’ understanding and learning evaluation tests. The data were analyzed using descriptive quantitative analysis by calculating the class average score, the percentage of learning mastery, and the percentage of students’ understanding in each cycle. The results showed that the implementation of the Jarimatika Snake and Ladder concrete teaching aid improved students’ understanding of basic arithmetic operations. The average score increased from 54 in the pre-cycle to 70.19 in Cycle I, and further increased to 83.67 in Cycle II. In Cycle II, 86% of students achieved scores ≥80, while 14% of students obtained scores between 75–79, indicating that all students had reached the minimum mastery criterion. In addition, the percentage of students’ understanding based on observation increased from 65.08% in Cycle I to 82.94% in Cycle II. These results indicate that the use of educational game-based learning media such as the Jarimatika Snake and Ladder is effective in improving elementary school students’ understanding of basic arithmetic operations in mathematics. Keywords: Learning Media, Jarimatika Snake and Ladder, Basic Arithmetic Understanding, Mathematics